A Closer Look at Cross‐functional R&D Cooperation for Innovativeness: Innovation‐oriented Leadership and Human Resource Practices as Driving Forces1. Issue 5 (6th December 2013) - Stock, Ruth Maria; Totzauer, Florian; Zacharias, Nicolas A.
<x xml:space="preserve">Abstract</x> Because cross‐functional research and development (R&D) cooperation appears to drive innovation, many firms have invested considerably in it. However, despite substantial efforts to improve information and communication infrastructures or to bring departments in closer proximity with one another, structural investments often fail to produce the desired positive impact on cross‐functional R&D cooperation. This failure may arise because firms undertaking these structural investments do not manage their employees adequately. Extant research acknowledges the importance of motivating and enabling members of the R&D function to cooperate with other functions. Yet empirical studies investigating the relative importance of leadership and different human resource (HR) practices for enhancing cross‐functional R&D cooperation are scarce. Drawing on the resource‐based view and organizational support theory, this study investigates how innovation‐oriented leadership and HR practices might support members of the R&D function and encourage cross‐functional R&D cooperation, which enhances product program innovativeness. Specifically, members of the R&D function who are supported in their innovation efforts through innovation‐oriented leadership and HR practices should reciprocate for the support they receive by intensifying their cross‐functional cooperation to achieve greater product program innovativeness. Relying on multi‐informant data from 125 firms with assessments from marketing and R&D managers, this study shows that innovation‐oriented leadership and HR practices have different effects on cross‐functional R&D cooperation. A structural equation modeling‐based analysis of the hypothesized relationships reveals that innovation‐oriented leadership, rewards, and training and development have considerable positive effects. In contrast, recruitment does not drive cross‐functional R&D cooperation. Because firms usually operate in dynamic markets, and increasingly acquire relevant information from customers when generating innovations, this study also considers market‐related dynamism and customer integration as important contingency factors. For firms facing market‐related dynamism and those relying on customer integration, leadership and training and development are particularly effective for enhancing cross‐functional R&D cooperation. By integrating two theoretical perspectives, this study not only advances knowledge on the antecedents of cross‐functional R&D cooperation, but also helps explain differences in their relative effectiveness. Furthermore, it both adds to the discussion of whether monetary rewards are appropriate means to foster innovation and challenges existing assumptions about the role of recruiting for innovation.